Uji Efek Analgetik Ekstrak Etanol Bunga Kecombrang (Etlingera elatior. jack) Terhadap Mencit Putih Jantan (Mus musculus) - Fita Selonni; Tuty Taslim (Jurnal Kesehatan Farmasi, 2022)
Background : Ibuprofen is a drug that is commonly used when the body experiences pain. In this study, the medicinal plant that will be tested for its analgesic effect on mice is Kecombrang flower. Methods: Kecombrang flowers were first used as ethanol extract with two different concentrations, namely 400 mg/kgBb and 800 mg/kgBb. The experimental animals used were 20 male white mice which were divided into 4 groups where each group consisted of 5 mice. Each group of mice was given a dose treatment first, then 30 minutes after that, 1.1% acetic acid solution was given via ip, after that, pay attention to the amount of writhing shown by the mice. Results: From the 2 concentrations of kecombrang flower ethanol extract given, it turned out that the 400 mg/kgBb dose group showed fewer stretches than the 800 mg/kgBb dose group, but the analgesic effect was still low compared to the control group + namely ibuprofen. Key words : Kecombrang flower, analgesic and mice